Design and Deployment of Swarm Engineering Systems: Insights, Challenges, and Innovations - Raza Muhammad Kazim; Guoxin Wang; Zhenjun Ming; Janet K. Allen; Farrokh Mistree (IEEE Access)
In this study, we explore the fundamentals of design and deployment of Multi-Agent Swarm Engineering Systems (MASESs), a comprehensive framework aimed at improving decision-making and operational efficiency in industrial environments. Swarm engineering systems draw inspiration from collective behaviors observed in natural swarms (such as ants or bees), offering a decentralized approach to problem-solving in complex systems. We provide a detailed theoretical foundation for MASES, focusing on key elements such as spatial control formation, adaptive coordination, decision-making dynamics, and critical factors such as scalability, adaptability, and robustness in practical applications. The analysis is enriched with insightful tables that highlight current innovations and challenges, underscoring the importance of balancing decentralization with scalability. In transitioning to practical applications, we discuss design methodologies and performance evaluation strategies, emphasizing the transformative potential of swarm engineering systems. Crucially, we highlight how artificial intelligence (AI) and machine learning (ML) are being integrated into MASES to enhance decision-making capabilities, adaptability, and scalability. Advanced frameworks and simulation environments have been shown to play a crucial role in ensuring that MASES operates effectively, fostering intelligence and adaptability to meet complex industrial demands. By showcasing various applications, we highlight the potential of MASES to enhance operational landscapes across industries and identify pathways for future research to refine and perfect this integration.